Impact of the Gap Between Social Workers' Work Interaction Frequency With Governments and Clients on Their Burnout in China: Mediating Effects of Role Conflict and Moderating Effects of Non-front-line Work - Wang, Jie; Tan, Zimin; Li, Jiajun; Wu, Qiang (Frontiers in Public Health, 2022)
Background: Since the 2000s, local governments have contracted out more and more social services to social work organizations in China. Social workers are thus experiencing inconsistency between local governments’ and clients’ demands and the deviation from the professional duty of helping clients, which may result in conflicting and unclear roles in their jobs and further lead to burnout. Based on the Role Stress-burnout Model and the previous theoretical and field-work investigations, this study examined the effects of the government-client work interaction frequency gap on social workers’ burnout as well as the mediating effects of role ambiguity and conflict and the moderating effects of the non-front-line work. Methods: A cross-sectional study of 2643 front-line social workers and 2599 supervisors or managers from 56 major cities all over China was conducted. Work burnout was measured by the 22-item three-dimension Maslach’s Burnout Inventory Scale. Rizzo et al.’s 14-item scale measured role conflict and ambiguity. The government-client working interaction frequency gap was measured by the difference between the five-point level of work interaction frequency with governments minus the one with clients. Structural equation modeling was adopted to test the mediation and moderation models. Results: Results showed that for the front-line social workers, besides directly reducing personal accomplishment, the government-client work interaction frequency gap could indirectly neutralize its alleviating effects on emotional exhaustion (Mediating effect ratio= -63.64 %), make its total effects on depersonalization significant (37.03%), and reduce personal accomplishment further (23.08%) through increasing social workers’ feeling of role conflict. However, the above mediating effects of role conflict were not significant for social workers with extra management or supervision workload, revealing the moderating effects of non-front-line work. Conclusions: This study revealed that front-line social workers in China who had more work interaction with governments and less with clients could have higher role conflict, increasing their burnout further. Therefore, social work educational programs should include adequate mental adjustment courses and practical emplacement to prepare students for the potential role conflict. Furthermore, higher-level governments should issue relevant regulations to form a collaborative rather than an employment relationship between local governments and social worker organizations.